Evaluation of the correlations between personality and parental monitoring with watching porn in male adolescents - Aliyari, Farshad; Kianimoghadam, Amir Sam; Bakhtiari, Maryam (Researcher Bulletin of Medical Sciences, 2024)
Objective: To reduce watching porn in adolescents, identifying its underlying factors is necessary. The purpose of this study was to examine the correlations between personality and parental monitoring with watching porn in male adolescents in Iran. Materials and Methods: This cross-sectional study was advertised on social media. 154 participants completed the self-reported questionnaires through online link. Analysis was performed to assess the kind of association by SPSS software version 26. Results: Results indicated that extroversion was significantly correlated with watching porn (rs = 0.179, p<0.05) and there weren’t any correlations between other personality traits and parental monitoring with it. Conclusion: These results emphasize the importance of extroversion in watching porn. Considering the large range of behaviors that make a person an extrovert, more studies are needed to examine extroversion and its characteristics more precisely to gain a better insight into this correlation.